Pipeline Pulsing Flow of Slurries - Hameed, Abdul (My University, 1983)
This thesis presents the results of pulsing flow experiments on solid-liquid suspensions. Specifically, the hydraulic energy requirement in pulsing flows for a given slurry flowrate is compared with the steady state energy consumption for the same flowrate. It is also shown theoretically that, for the same time-averaged flowrate as in the steady state case, it is feasible to reduce the time-averaged pressure gradient and hence power requirement by pulsing.
The following five different types of flow systems were the subject of study: water, bentonite clay water, fine sand water, fine sand bentonite clay water and coarse sand water.
For the above five types of flow systems the following pertinent flow variables were studied: pulsation frequency, pulsation amplitude, average slurry velocity, solids volume concentration, mean particle size and the presence of a small amount of ultra fine particles in coarse solid liquid mixtures.
The experimental results of pulsing flow of water alone indicated that the pulsing to steady state power ratio (Jᴘ/Js) was always greater than unity indicating that for a Newtonian fluid the hydraulic energy in pulsing flow is greater than the steady flow, the increase of energy being used to maintain pulsation.
Results of pulsing flow experiments with bentonite slurry have indicated that the power ratio (Jᴘ/Js) was observed to be less than unity for certain combinations of frequency, amplitude and slurry velocity. The minimum value of (Jᴘ/Js) found was about 0.75 at a frequency of about 0.80 Hz, amplitude of 51 mm and velocity of 1.9 m/s.
In the ranges investigated, results with sand-water slurries have indicated that the power ratio (Jᴘ/Js) was a function of the variables listed above. The minimum value of the power ratio (Jᴘ/Js) for sand water slurries was found to be about 0.50 at the following values of the variables: pulsation frequency 0.45 Hz, amplitude 32 mm, slurry average velocity 1.8 m/s, solids volumetric concentration 12.5% and particle size 0.47 mm.
The reduction in the power ratio in the case of pulsing flow of sand water slurries is attributed to the formation of a particle free layer near the pipe wall while the bulk of the particles flow as a plug in the middle of the annulus of the lubricating particle free layer.
In the case of bentonite clay water slurry the reduction in the power ratio is attributed to the formation of a low viscosity layer near the pipe wall. The bulk of the slurry flows as a plug in the middle of the annulus of the low viscosity layer.
Results of this thesis indicate that power consumption for transport of slurries using pulsing flow is considerably less than power required to transport the same amount of slurry by a steady flow method.
Keywords: Mechanical Engineering; Mechanical Engineering